Faktor-Faktor yang Mempengaruhi Minat Institusi Pendidikan dalam Menerapkan Sistem Pembayaran Online - Rosdwianty, Sintya; Najib, Mukhamad; Jahroh, Siti (Universitas Diponegoro, 2020)
The growth of financial technology is increasing very rapidly, followed by the number of players in this industry. However, society’s digital literacy still needs to be developed. PT Infra Digital Nusantara is one of financial technology start-up that focuses on online payment transactions in the education sector. Offering the financial system, especially online payment to an education institution, yet PT IDN is still struggling to gain new customers. In this study, the factors that affecting the interest and needs to implement online payment for education sectors were analyzed. Data processing was performed using the method of Structural Equation Modelling-Partial Least Square (SEM PLS). Target survey respondents were the customers of PT IDN. The results showed that Perceived Usefulness, Perceived Ease of Use, Attitude towardUsingTechnology, and Behavior Intention to Use had significant factors in affecting The Actual Use of the System. This is indicated by t-valuesof all hypotheses are above 1.96 at the 95% significance level.Hence, Perceived Usefulness, Perceived Ease of Use of the system and Attitude toward Using Technology, as the key determinant factors of technology acceptance, needs to be maintained carefully.